Evidências financeiras e mercadológicas na construção da reputação corporativa: uma análise a partir das expectativas dos Stakeholders - Oliveira, Talyta Eduardo (2023)
Corporate reputation is the basis of customer and investor confidence, and failure to meet their expectations can directly reflect on the company's image in the market. On the other hand, expenses to meet these stakeholders' expectations should not compromise the organization's financial health. Thus, the thesis defended here is that a company's quest to meet the expectations of customers and investors, without considering its own financial performance, can compromise its corporate reputation. This thesis analyzes the largest Brazilian retail company: Lojas Americanas and has the general objective of investigating whether a company's quest to meet the expectations of investors and customers, without considering its own financial performance, can compromise its corporate reputation. A qualitative research was developed, with primary and secondary data collection. Firstly, using secondary data, Americanas' reputation was investigated based on the expectations of investors and customers, before and after the disclosure of the scandal. Then, the collection of primary data was carried out, through a survey with Americanas buyers to understand the expectations of the company's customers in order to identify the company's corporate reputation for this public. The results show that the company's effort to remunerate its investors through interest on equity and to attract customers with low prices and constant sales promotions, even with high debt and low liquidity, may have contributed to the poor financial performance. The recent financial scandal may be a consequence of the accumulation of financial problems over time, however, as it deals with a recent case, this thesis does not intend to explain the fact, but seeks to understand it in the light of theories and evidence from the Marketplace. It is concluded that the company's corporate reputation is maintained for customers regardless of the company's financial performance, if their expectations are being met. On the other hand, it was possible to assess that the low liquidity, the increase in the company's debt and the reduction in net income are factors that may have contributed to the recent economic crisis of Americanas S.A situation that impacted investor confidence and, consequently, reduced the reputation of the company for this group of stakeholders